2017
DOI: 10.1016/j.chembiol.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Deacylation Mechanism by SIRT2 Revealed in the 1′-SH-2′-O-Myristoyl Intermediate Structure

Abstract: Summary Sirtuins are NAD-dependent deacylases. Previous studies have established two important enzymatic intermediates in sirtuin-catalyzed deacylation, an alkylamidate intermediate I, which is then converted to a bicyclic intermediate II. However, how intermediate II is converted to products is unknown. Based on potent SIRT2-specific inhibitors we developed, here we report crystal structures of SIRT2 in complexes with a thiomyristoyl (TM) inhibitor and carba-NAD or NAD. Interestingly by soaking crystals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 34 publications
5
41
0
Order By: Relevance
“…ChemMedChem 2019, 14,744 -748 www.chemmedchem.org reported crystal structure of SIRT2 in complexw ithamyristoyl peptide( PDB ID:4 X3O), suggested that the introduction of a hydroxy group on TM allowed the compound to form hydrogen bonds with the amino acid backbone of SIRT2, specifically with Gln265, Val266, and Asn267 (Figure 3). [11] Similarh ydrogen bonds were also observed when am odel wasg enerated with JH-T4 and the established SIRT3 and H3K9 myristoyl peptide crystal structure,5 BWN ( Figure S1). [9a] The ability to form hydrogen bonds makes JH-T4 am ore efficient suicide substrate, which leads to the increased inhibition of SIRT1 andS IRT3,a s well as better inhibition of the defatty-acylation activity of SIRT2.…”
mentioning
confidence: 61%
“…ChemMedChem 2019, 14,744 -748 www.chemmedchem.org reported crystal structure of SIRT2 in complexw ithamyristoyl peptide( PDB ID:4 X3O), suggested that the introduction of a hydroxy group on TM allowed the compound to form hydrogen bonds with the amino acid backbone of SIRT2, specifically with Gln265, Val266, and Asn267 (Figure 3). [11] Similarh ydrogen bonds were also observed when am odel wasg enerated with JH-T4 and the established SIRT3 and H3K9 myristoyl peptide crystal structure,5 BWN ( Figure S1). [9a] The ability to form hydrogen bonds makes JH-T4 am ore efficient suicide substrate, which leads to the increased inhibition of SIRT1 andS IRT3,a s well as better inhibition of the defatty-acylation activity of SIRT2.…”
mentioning
confidence: 61%
“…The exchange of positions of F60 and W67 induced by the crotonyl group in CobBac2 leads to the accumulation of Int. III (38), probably by preventing its hydrolysis due to increased shielding against water. This conclusion is supported by the observation that the equivalent of F60 (F33) in Thermotoga maritima Sir2 shields the reaction intermediates from premature hydrolysis and ADP-ribose formation (16), and that the equivalent of W67 (Y40) is predicted by MD simulations to control the access of water to the active site (42).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained crystals of the complex by co-crystallization after 16 h ( Figure 4A) and by soaking for 36 h ( Figure 4B). We observed a continuous density that linked the ADP-ribose moiety to the crotonyl group via the 2'-OH of the ribose ( Figure 4B (38). We modelled the analogous crotonyl-Int.…”
Section: Crystal Structure Of Butyryl-specific Cobbmentioning
confidence: 97%
“…Covalent modification of proteins is a powerful way to modulate macromolecular functions (Yang et al, 2016), representing a pivotal target for chemico-biological interventions (Jongkees et al, 2017;Mulder et al, 2016;Wang et al, 2017). Protein modifications may be regulated in a spatial-temporal manner by adaptor proteins, which function by modulating protein-protein interactions (Koch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%